GENERAL REQUIREMENTS FOR MANUSCRIPTS | BENDRIEJI REIKALAVIMAI RANKRAŠČIAMS - Mačianskienė, Nemira (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
Articles are submitted electronically at the following address http://uki.vdu.lt/smArticles follow the 7th edition of Publication Manual of the American Psychological Association (APA*) and are subjected to double peer-review and selected for publication on the basis of the following criteria: • the study is thematically relevant to the aim of the journal; • original, previously unpublished, not submitted to other journals during the evaluation process, ethical parameters highlighted; • presents empirical analysis or in-depth theoretical consideration; • contains basic structural elements:o Empirical study – introduction, background, aim, research parameters (sample, method, instrument), ethics, findings, discussion, conclusions, implications, references.o Conceptual study – introduction, background, aim, method, ethics, reflection and discussion, conclusions, insights, references. • focuses on an acute research problem;• is of adequate stylistic and linguistic quality.